Improving cerebral oxygenation, cognition and autonomic nervous system control of a chronic alcohol abuser through a three-month running program - Cabral, Daniel Aranha (Addict Behav Rep, 2017)
The abusive use of alcohol has shown to be associated to cerebral damage, impaired cognition, poor autonomic nervous control, impaired cardiovascular health, increased levels of stress and anxiety, depression symptoms and poor quality of life. Aerobic exercise has shown to be an efficient tool to reduce and overcome these issues. In this case report, a patient (forty-four years old, male) under treatment in public psychiatric hospital, classified as having a substance use disorder, underwent a three-month running program. The maximal oxygen consumption increased from 24.2 ml/kg/min to 30.1 ml/kg/min, running time increased from 6 min to 45 min (650%) and distance covered from 765 m to 8700 m (1037.2%). In prefrontal cortex oxygenation, oxyhemoglobin levels improved by 76.1%, deoxyhemoglobin decreased 96.9% and total hemoglobin increased 78.8% during exercise. Reaction time in the cognitive test during rest decreased 23%, and the number of correct answers increased by 266.6%. Parasympathetic cardiac parameters increased in several heart rate variability indices. Thus, we conclude that running exercise performed by an alcoholic patient hospitalized in a psychiatric hospital improves cerebral function, cognition and cardiovascular health.